Ulasan Implementasi sebuah Business Model Di PT. Sakti Persada Raya - Adeline Agoes (Bina Nusantara University, 2012)
In this economic world of business in Indonesia, Jakarta is one of the cities that supports the industry which now is growing quite fast with the development of many establishments. However, it is unfortunate that some of those establishments could not survive long facing the competition. One of the reasons that might causethat to happen is because of the lack of preparation in the Business Model. This journal will briefly discuss what are the definition and the importance of a Business Model which will be described in more detail with a real Business Model implemented by PT. SAKTI PERSADA RAYA.